FORMULATION OF SUNGKAI LEAF ETHANOL EXTRACT POWDER (Peronema canescens Jack.) AND ITS ANTIOXIDANT TEST - Sandra Tri Juli Fendri; Farida Rahim; Ririn Khairani; Siska Ferilda; Suryani (JURNAL KATALISATOR, 2023)
Sungkai leaves (Peronema canescens Jack.) is one of the medicinal plants that have antioxidant activity. This study aims to formulate sungkai leaf ethanol extract in the form of instant powder as a health supplement and test the antioxidant activity of   instant   powder   preparations.   Making   dry extract of sungkai leaves   using freeze dryer and antioxidant activity test using DPPH method at a maximum absorption wavelength of 520 nm. The results of instant powder formulation on organoleptis examination instant powder is in the form of fine powder, white with green grains, distinctive smell and slightly sweet taste while the brewed instant powder is in the form of a green liquid, distinctive smell and slightly sweet taste, good flow properties, flow speed 6.63 g / s, resting angle  29.45o,  soluble  time  110  seconds,  water insoluble part 1.528%, moisture content 5.12%, ash content 0.29% and pH 5.59. From all examinations have met the requirements of good preparations. IC values of50 ethanol extract and instant powder were 73.76 ppm and 662.69 ppm respectively. So it can be concluded that sungkai leaf ethanol extract can be formulated as instant powder and sungkai leaf ethanol extract has strong antioxidant activity, while sungkai leaf instant powder has very weak antioxidant activity.